Transdiagnostic-focused apps for depression and anxiety: a meta-analysis - Jake Linardon; Cleo Anderson; Mariel Messer; Claudia Liu; John Torous (npj Digital Medicine)
Abstract Mental health apps that adopt a transdiagnostic approach to addressing depression and anxiety are emerging, yet a synthesis of their evidence-base is missing. This meta-analysis evaluated the efficacy of transdiagnostic-focused apps for depression and anxiety, and aimed to understand how they compare to diagnostic-specific apps. Nineteen randomized controlled trials (N = 5165) were included. Transdiagnostic-focused apps produced small post-intervention effects relative to controls on pooled outcomes related depression, anxiety and distress (N = 23 comparisons; g = 0.29; 95% CI = 0.17–0.40). Effects remained significant across various sensitivity analyses. CBT apps and apps that were compared with a waitlist produced larger effects. Significant effects were found at follow-up (g = 0.25; 95% CI = 0.10, 0.41). Effects were comparable to disorder-specific app estimates. Findings highlight the potential of transdiagnostic apps to provide accessible support for managing depression and anxiety. Their broad applicability highlights their public health relevance, especially when combined with in-person transdiagnostic therapies to create new hybrid care models.